Irrigation scheduling advice: Egypt - Brouziyne, Youssef; El-Sayed, M.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The IRrigation Water Information Application (IRWI App) is a mobile application that helps farmers in Egypt’s Delta region increase water productivity and improve the irrigation efficiency of selected crops.